Weed plants associated with rain-fed maize crops in saline soils of the Lake Cuitzeo shore, Michoacán, Mexico - Sánchez-Blanco, Judith; Guevara-Féfer, Fernando (Instituto de Ecología, A.C., 2013)
We sampled the weed communities of rain-fed maize growing in soils with salinity problems during the 1996 agricultural cycle in ten sites at the Lake Cuitzeo shore. We found 133 species belonging to 94 genera and 34 families. The families with most species were Compositae, Gramineae, Euphorbiaceae, Solanaceae and Leguminosae, together representing more than half of the specific diversity, 63.89%. Dicotyledons represent 74.43% of the species, while 25.56% are Monocotyledons. Weed diversity in our study sites appear to be lower than the average diversity found in non saline sites in other areas of the Cuitzeo basin. 17.3% (23) of the species are introduced; while the remainder are plants native to the Americas 82.7% (110), principally Mexico and adjacent areas. The predominant life form is annual with 60.90%, followed by the perennial forms with 26.32%; the rest are facultative like annual-perennials 10.53% and annual-biannuals 2.25%. The floristic similarity among the sites using the Index of Sorensen varied from 0.507 to 0.083. No composition and diversity species correlation was found with physical-chemical factors of soils; however, some species showed preference to specific soil pH and texture.